One Out of Five Women Practiced Cervical Cancer Screening in Felege Hiwot Referral Hospital, Amhara, North West Ethiopia - Tenagnework, Antefe Abebe; Berhanu, Elfu; Abel, Lule Tessema; Mulusew, Alemneh Sinishaw (Journal of Cervical Cancer, 2021)
Background Eighty five percent of cervical cancer occurrence in resource-poor countries. Contributing factors for these are inadequate knowledge about the disease, early initiation of sexual intercourse and multiple sexual partners. Early screening is an intervention in reduction of maternal deaths due to cervical cancer. Consequently this study was conducted aiming to find out about the practice of cervical cancer screening and its associated factors. Methods A facility based cross sectional study was conducted using a pretested structured questionnaire among women attended Maternal and Child Health (MCH) department of Felege Hiwot Referral Hospital (FHRH) from March15 to April 15, 2019. The study participants were selected systematically. The collected data were entered and analyzed using SPSS version 20. Logistic regression analysis was employed to examine factors association with cervical cancer screening that was confirmed using AOR with its 95% CI. Results A total of 400 study participants were included with a response rate of 99.5%. Of the total study participants only 78 (19.5%; 95% CI: 15.6, 23.4) practiced screening for cervical cancer. The cervical cancer screening practice was affected by age (AOR=2.025; 95% CI: 1.118, 3.668). Of those women who had ever heard of about cervical cancer were seven fold more likely to practice cervical screening (AOR=6.924; 95% CI: 1.602, 29.928) compared to those who did not have any information before. Moreover, knowing genital tract discharge as a problem of female organ implement fourfold more likely compared to that of knowing nothing about problem of genital tract (AOR=3.766; 95% CI: 1.761,8.055). Conclusion and Recommendation The study depicted there was low utilization of cervical cancer screening. Awareness creation about cervical cancer and knowledge of genital tract problems had positive influence for screening practice.
Keywords: Cervical cancer; screening Practice of cervical cancer